Community and Global Ecology of Deserts - Hufnagel, Levente (IntechOpen, 2018)
The aim and purpose of our book, Community and Global Ecology of Deserts, is to give an overview and report from the frontiers of desert ecological research. The ecology of deserts as a scientific discipline plays a key role in solving many of global problems due to collective adaptation methods and approaches of lifeforms living in extreme environments. If ecologists or environmental scientists are talking about desert ecological research, then almost everyone is thinking about specific desert flora, fauna, or desertification itself as a consequence of climate change, or sand dune-triggered disasters. In fact, the importance of ecological research in deserts is far more general and broader. We hope that our book will be interesting and useful for researchers, lecturers, students and anybody interested in this field.